Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
[tex]x = 11[/tex]
Step-by-step explanation:
[tex]7x - 9 = 28 + 4(x - 1) \\ 7x - 9 = 28 + 4x - 4 \\ 7x - 4x = 28 - 4 + 9 \\ 3x = 33 \\ \\ x = \frac{33}{3} \\ \\ x = 11[/tex]
Answer:
c) x = 11
Step-by-step explanation:
Given equation: 7x - 9 = 28 + 4(x - 1)
Steps:
1. Distribute 4 through the parentheses:
7x - 9 = 28 + 4(x) + 4(-1)
7x - 9 = 28 + 4x - 4 [simplify]
7x - 9 = 24 + 4x
2. Subtract 4x from both sides:
7x - 4x - 9 = 24 + 4x - 4x
3x - 9 = 24
3. Add 9 to both sides:
3x - 9 + 9 = 24 + 9
3x = 33
4. Divide both sides by 3:
3x ÷ 3 = 33 ÷ 3
x = 11
5. Check your work:
7x - 9 = 28 + 4(x - 1) [substitute 11 for x]
7(11) - 9 = 28 + 4(11 - 1) [simplify]
77 - 9 = 28 + 4(10) [simplify]
68 = 28 + 40 [add]
68 = 68 ✔
Learn more here:
brainly.com/question/27844321
brainly.com/question/21222758
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.